Implementasi Algoritma Greedy pada Rute Wisata Danau Tao Desa Batang Onang Baru Berbasis Website - Siregar, Riska Novasari; Aulia, Rahmat; Siregar, Rosyidah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to facilitate the travel of tourists visiting Tao Lake and increase travel efficiency by determining the fastest route. One of the methods used to determine the fastest route to Tao Lake is the greedy algorithm method. The advantage of the greedy algorithm is that it is fast in acting and does not take long to consider the consequences of what is decided so that it is very easy to implement in several existing problems. This website was created for the Gunung Tua and Padang Sidempuan areas. The results of the trial of the Tao Lake tourism website using a black box stated that the results of the website's feasibility point were 54% strongly agree, 26% agree, 14% disagree and 6% strongly disagree. The results of the website user satisfaction point were 58% strongly agree, 32% agree, 6% disagree and 4% strongly disagree.